Enterococcus faecalis Bearing Aggregation Substance Is Resistant to Killing by Human Neutrophils despite Phagocytosis and Neutrophil Activation - Rakita, Robert M. (American Society for Microbiology, 1999)
Enterococcus faecalis aggregation substance (AS) mediates efficient bacterium-bacterium contact to facilitate plasmid exchange as part of a bacterial sex pheromone system. We have previously determined that AS promotes direct, opsonin-independent binding of E. faecalis to human neutrophils (PMNs) via complement receptor type 3 and other receptors on the PMN surface. We have now examined the functional consequences of this bacterium-host cell interaction. AS-bearing E. faecalis was phagocytosed and internalized by PMNs, as determined by deconvolution fluorescence microscopy. However, these bacteria were not killed by PMNs, and internalized bacteria excluded propidium iodide, indicating intact bacterial membranes. Resistance to killing occurred despite activation of PMNs, as indicated by an increase in both functional and total surface Mac-1 expression, shedding of l-selectin, and an increase in PMN extracellular superoxide and phagosomal oxidant production. Deconvolution fluorescence microscopy also revealed that phagosomes containing AS-bearing bacteria were markedly larger than phagosomes containing opsonized E. faecalis, suggesting that some modification of phagosomal maturation may be involved in AS-induced resistance to killing. PMN phagosomal pH was significantly higher after ingestion of nonopsonized AS-bearing E. faecalis than after that of opsonized bacteria. The novel ability of AS to promote intracellular survival of E. faecalis inside PMNs suggests that AS may be a virulence factor used by strains of E. faecalis.